2010
DOI: 10.1111/j.1462-2920.2010.02369.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium promotes exopolysaccharide phase variation and biofilm formation of the resulting phase variants in the human pathogen Vibrio vulnificus

Abstract: Vibrio vulnificus is a Gram-negative bacterium found in estuaries and coastal waters and is associated with human disease caused by ingestion of raw shellfish. Pathogenesis is directly related to the presence of capsular polysaccharide (CPS). Encapsulated virulent strains exhibit an opaque colony phenotype, while unencapsulated attenuated strains appear translucent. A third colony type, rugose, is caused by expression of rugose extracellular polysaccharide (rEPS) and forms robust biofilms. Vibrio vulnificus un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 30 publications
2
57
0
1
Order By: Relevance
“…Previous research has shown that increasing amounts of calcium disable Bap-mediated biofilm formation and intercellular adhesion of Staphylococcus aureus (1). However, recent reports indicate that calcium promotes biofilm formation in other microorganisms, such as Xyllela fastidiosa or Vibrio vulnificus (4,7). Therefore, calcium may modulate biofilm formation in opposite ways in different bacteria, but the molecular basis for its role remains unclear.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Previous research has shown that increasing amounts of calcium disable Bap-mediated biofilm formation and intercellular adhesion of Staphylococcus aureus (1). However, recent reports indicate that calcium promotes biofilm formation in other microorganisms, such as Xyllela fastidiosa or Vibrio vulnificus (4,7). Therefore, calcium may modulate biofilm formation in opposite ways in different bacteria, but the molecular basis for its role remains unclear.…”
mentioning
confidence: 87%
“…Calcium has been related to a variety of biological processes in bacteria (4,7,10), but its role in biofilm development is somewhat controversial. Previous research has shown that increasing amounts of calcium disable Bap-mediated biofilm formation and intercellular adhesion of Staphylococcus aureus (1).…”
mentioning
confidence: 99%
“…Environmental or intracellular stress conditions that result in DNA supercoiling can modify phase variation switching frequency (445). Some systems are regulated by information about the cell's location, outside or within a host or a tissue, that can be given by the temperature (446,447) or the composition of the environment (pH [448], carbon sources [449], oxygen [450] and iron [451] levels, amino acid concentrations [446], or the presence of specific elements [452]). Certain mechanisms answer to eukaryotic host-specific signal molecules, such as the presence of sialic acid, which is released by the host as a defense mechanism (453).…”
Section: Consequences Of Genome Instability In Bacteria Phase and Antmentioning
confidence: 99%
“…A correlation between polysaccharide production and biofilm formation has been demonstrated in V. vulnificus, V. cholerae, V. parahaemolyticus, and V. fischeri under aerobic conditions; however, this relationship has yet to be investigated anaerobically (40,(43)(44)(45)(46). The genome of V. vulnificus contains multiple highly conserved polysaccharide loci, including those that produce exopolysaccharides (EPS), lipopolysaccharides (LPS), and capsular polysaccharides (CPS) (31,33,34,36,(47)(48)(49). EPS has been shown to correlate positively with biofilm formation in V. vulnificus (50), but previously a negative relationship between CPS and biofilm formation aerobically in this bacterium, as well as other Vibrio species, has been described (43,44,51).…”
mentioning
confidence: 99%
“…Encoded in these operons are three highly conserved genes, wza wzb and wzc, involved in transport of polymers across the outer membrane of the cell (31,33,34). Environmental conditions have been previously shown to initiate differential regulation of group 1 CPS genes and play a role in phase variation in this bacterium as well as other human pathogens (29,32,35,36). It is important to understand the regulation of CPS genes in V. vulnificus during anaerobiosis, a condition it encounters in its natural environment and in the human host (14,15,37).…”
mentioning
confidence: 99%